Satisfaction with orthodontic treatment: cross-cultural adaptation and validation of an instrument for the Brazilian Portuguese language - Renata Negreiros ALVARENGA; Saul Martins PAIVA; Carlos FLORES-MIR; Eduardo BERNABÉ; Lucas Guimarães ABREU (Dental Press Journal of Orthodontics, 2023)
ABSTRACT Objective: To cross-culturally adapt into the Brazilian Portuguese and evaluate the psychometric properties of an instrument for assessing the satisfaction of parents/guardians regarding their sons’/daughters’ orthodontic treatment. Methods: Translations of the instrument from English, pre-test and evaluation of validity and reliability of the Brazilian Portuguese version were performed. The questionnaire has 25 items distributed across 3 subscales (process, psychosocial effect and outcome). Eighty-three parents/guardians of children/adolescents who had completed orthodontic treatment participated. Descriptive statistics and floor and ceiling effects were calculated. Internal consistency, stability (interval of three weeks), convergent construct validity and discriminant construct validity were determined. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) assessed dimensionality. Results: Among the 83 parents/guardians, 58 (69.9%) were mothers and 25 (30.1%) were fathers of children/adolescents. In the questionnaire’s total score and the three subscales scores, an acceptable percentage (≤15%) of participants achieved the maximum score (ceiling effect). In the total questionnaire score and in the three subscales scores, no participant achieved the minimum score (floor effect). Cronbach’s α coefficient for the total score was 0.72 (internal consistency). Intra-class correlation coefficient for the total score was 0.71 (stability). The questionnaire’s total score presented large Pearson correlation coefficient (>0.50) with the three subscales too (construct validity). Female parents/guardians had significantly higher scores in the psychosocial effect (p=0.013) and in the treatment outcome (p=0.037) subscales, compared to male parents/guardians (discriminant validity). EFA and CFA confirmed dimensionality in a three-factor solution. Conclusions: The final obtained version is valid and reliable to be used in Brazilian populations.